Investigation on vehicle dynamic behaviour during emergency braking at different speed - I. M., Zulhilmi; Mohamad Heerwan, Peeie; R. I. M., Eiman; Muhammad Izhar, Ishak; S. M., Asyraf (Universiti Malaysia Pahang, 2019)
Safety system of the vehicle can be divided into two main categories; passive and active safety system. The purpose of the passive safety system is to protect the occupant during an accident, while active safety system allows the vehicle to be manoeuvred to avoid any collision. Although active safety system can prevent the accident, in a critical situation such as emergency braking, the dynamic behaviour of the vehicle changes abruptly, and the vehicle becomes unstable. The objective of this study is to analyse the dynamic behaviour of the vehicle during emergency braking with and without anti-lock braking system (ABS). In this study, the dynamic behaviour of the vehicle is observed by the simulation model that has been developed in the MATLAB-Simulink. The analysis vehicle model is Universiti Malaysia Pahang (UMP) test car, model Proton Persona. During braking, when ABS control unit detect the wheel is to lock-up, the hydraulic control unit closed the hydraulic valve to release the brake pad on the wheel. This allows the wheel to spin intermittently during braking. From the simulation results, when ABS is not applied to the vehicle, the front tires were lock-up and the vehicle become skidding. However, when ABS is applied, the speed of all tires decreased gradually and the vehicle is not skidding. The simulation results also show that the stopping distance with ABS is improved 28% compared without ABS.